Development of carboxymethyl cellulose-chitosan hybrid micro- and macroparticles for encapsulation of probiotic bacteria. (1st November 2017) - Singh, P.; Medronho, B.; Alves, L.; da Silva, G.J.; Miguel, M.G.; Lindman, B.
Highlights: Novel promising biobased matrices for probiotic bacteria encapsulation and delivery. Physical and chemical particles of chitosan, carboxymethylcellulose and genipin. Physico-chemical, swelling and morphological properties characterized. Micro and macroparticles with comparable structural features. Probiotic bacteria successfully trapped into the particles with acceptable viability. Abstract: Novel carboxymethyl cellulose-chitosan (CMC-Cht) hybrid micro- and macroparticles were successfully prepared in aqueous media either by drop-wise addition or via nozzle-spray methods. The systems were either physically or chemically crosslinked using genipin as the reticulation agent. The macroparticles (ca. 2 mm) formed are found to be essentially of the core-shell type, while the microparticles (ca. 5 μm) are apparently homogeneous. The crosslinked particles are robust, thermally resistant and less sensitive to pH changes. On the other hand, the physical systems are pH sensitive presenting a remarkable swelling at pH 7.4, while little swelling is observed at pH 2.4. Furthermore, model probiotic bacteria ( Lactobacillus rhamnosus GG) was for the first time successfully encapsulated in the CMC-Cht based particles with acceptable viability count. Overall, the systems developed are highly promising for probiotic encapsulation and potential delivery in the intestinal tract with the purpose of modulating gut microbiota and improving human health.